STUDI EKSPERIMENTAL DAN PEMODELAN MATEMATIKA PROSES PENGERINGAN KAKAO ENERGI SURYA SECARA INTERMITTENT - Haznam Putra; Farel H. Napitupulu; Himsar Ambarita; Siti Farah Dina (Cylinder : Jurnal Ilmiah Teknik Mesin, 2014)
In this research, the behavior of cocoa drying using solar dryers have been studied. Experiments conducted on drying cocoa beans that have been fermented first. Cocoa plantations are taken from the area around North Sumatra - Indonesia. Solar energy is used as a source of energy that save and clean for drying. Cocoa is a mainstay in Indonesian commodities, but the quality of the current generated is relatively low. As the aims of this research is gain quality with mathematical modeling of drying by producing good quality cocoa. Preparation phase starts from cocoa fermentation process. With some testing times cocoa taken one test where the results of fermented cocoa that has been washed and dried from water content 55.83% to 7.01% (db), which lasted for 3 (three) days ie, 22 to 24 April 2013 from at 7:00 to 17:00 pm (intermittent). The study was conducted at the Solar Energy Laboratory, Faculty of Engineering Department of Mechanical Engineering of North Sumatra University Medan. It is located in Medan city with the position of 33.6 ° N - 98.4 ° W, altitude 200 meters above sea level and meridian time (GMT +7). From the experimental results obtained experimental equation mathematical model for intermittent drying of cocoa, with the value being the value of the diffusivity coefficient of 1.39 x 10^-10 to 1.85 x 10^-10 m^2/sec, besides the quality of the dried cocoa in this study better than dried cacao directly under the sun.